2020
DOI: 10.1002/lary.29053
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Primary Tumor Surgical Resection in Distant Metastatic Carcinomas of the Thyroid

Abstract: Objectives/Hypothesis Thyroid cancer with distant metastasis (TCDM) at diagnosis has significantly worse survival rates when compared to localized/regional thyroid cancer. This study sought to report on the characteristics of patients presenting with TCDM and the potential survival advantage of surgical resection. Study Design Data were acquired from the Surveillance, Epidemiology, and End Results (SEER) database with cases from 2004 to 2015. Methods TCDM cases (n = 2,558) were identified from the SEER databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
2
0
0
Order By: Relevance
“…We excluded SPM diagnosed within 12 months of the thyroid cancer diagnosis, which may be another important cause. In addition,, patients with stage regional and distant had greater CSM than localized in the no-RAI group, RAI was associated with improved CSM particularly in distant metastatic thyroid cancer, it was consistent with previous studies (30,31). We found that the mortality rate after RAI treatment is higher than that of no-RAI in all subgroups except for regional and distant metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…We excluded SPM diagnosed within 12 months of the thyroid cancer diagnosis, which may be another important cause. In addition,, patients with stage regional and distant had greater CSM than localized in the no-RAI group, RAI was associated with improved CSM particularly in distant metastatic thyroid cancer, it was consistent with previous studies (30,31). We found that the mortality rate after RAI treatment is higher than that of no-RAI in all subgroups except for regional and distant metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, patients in the RAI group with regional or distant stage had lower CSM compared to those in the non-RAI group, especially in patients with distant metastatic thyroid cancer. These results indicate that RAI treatment may improve thyroid CSM, it was consistent with previous studies [31,32]. We found that the mortality rate after RAI treatment was higher than that of non-RAI in all subgroups except for regional and distant metastasis.…”
Section: Original Papersupporting
confidence: 93%